17
$\begingroup$

I have recently met with this integral: $$\int_0^1 \frac{\ln(1+x^a)}{1+x}\, dx$$

I want to evaluate it in a closed form, if possible.

1st functional equation:

$\displaystyle f(a)=\ln^2 2-f\left ( \frac{1}{a} \right )$ since: $$\begin{aligned} f(a)=\int_{0}^{1}\frac{\ln (1+x^a)}{1+x}\,dx &= \int_{0}^{1}\ln \left ( 1+x^a \right )\left ( \ln (1+x) \right )'\,dx\\ &= \ln^2 2 - \int_{0}^{1}\frac{ax^{a-1}\ln (1+x)}{1+x^a}\,dx\\ &\overset{y=x^a}{=\! =\! =\!}\ln^2 2 - \int_{0}^{1}\frac{a y^{(a-1)/a}\ln \left ( 1+y^{1/a} \right )}{1+y}\frac{1}{a}y^{(1-a)/a}\,dy \\ &= \ln^2 2 -f\left ( \frac{1}{a} \right ) \end{aligned}$$

2nd functional equation:

$\displaystyle f(a)=-\frac{a\pi^2}{12}+f(-a)$ since:

$$\begin{aligned} f(a)=\int_{0}^{1}\frac{\ln (1+x^a)}{1+x}\,dx &=\int_{0}^{1}\frac{\ln \left ( x^a\left ( 1+x^{-a} \right ) \right )}{1+x}\,dx \\ &= a\int_{0}^{1}\frac{\ln x}{1+x}\,dx+\int_{0}^{1}\frac{\ln (1+x^{-a})}{1+x}\,dx\\ &= a\int_{0}^{1}\frac{\ln x}{1+x}\,dx+f(-a)\\ &= a\int_{0}^{1}\ln x \sum_{n=0}^{\infty}(-1)^n x^n \,dx +f(-a)\\ &= a\sum_{n=0}^{\infty}(-1)^n \int_{0}^{1}\ln x \cdot x^n \,dx +f(-a)\\ &=\cdots\\ &=-\frac{a\pi^2}{12}+f(-a) \end{aligned}$$

What I did try was:

1st way $$\begin{aligned} \int_{0}^{1}\frac{\log(1+x^a)}{1+x}\,dx &=\int_{0}^{1}\log(1+x^a)\sum_{n=0}^{\infty}(-1)^n x^n\,dx \\ &= \sum_{n=0}^{\infty}(-1)^n \int_{0}^{1}\log(1+x^a)x^n\,dx\\ &= \sum_{n=0}^{\infty}(-1)^n \{ \left[ \frac{x^{n+1}\log(1+x^a)}{n+1} \right]_0^1- \\ & \quad \quad \quad \quad \quad \frac{a}{n+1}\int_{0}^{1}\frac{x^{n+1}x^{a-1}}{1+x^a}\,dx \} \end{aligned}$$

2nd way I tried IBP but I get to an unpleasant integral of the form $\displaystyle \int_{0}^{1}\frac{\ln(1+x)x^{a-1}}{1+x^a}\,dx$.

3nd way It was just an idea ... expand the nominator into Taylor Series , swip integration and summation and get into a digamma form . This way suggests that a closed form is far away ... since we are dealing with digammas here.

The result I got was: $$\begin{aligned} \int_{0}^{1}\frac{1}{1+x}\sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k}x^{ak} &=\sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k}\int_{0}^{1}\frac{x^{ak}}{1+x}dx \\ &= 1/2\sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k}\left[\psi\left(\frac{ak}{2}+1\right)-\psi\left(\frac{ak}{2}+1/2\right)\right] \\ \end{aligned}$$ and I can't go on.

$\endgroup$
3
  • 2
    $\begingroup$ These three links contain a wealth of information, and so do these two. $\endgroup$
    – Lucian
    Mar 18, 2015 at 11:32
  • $\begingroup$ See this paper for the general results about this integral (and a nice list of closed form solutions) $\endgroup$
    – Yuriy S
    Mar 10, 2016 at 17:11
  • $\begingroup$ The first functional equation appears to only be true if $a>0$ $\endgroup$
    – Jacob
    May 13, 2016 at 16:11

1 Answer 1

1
$\begingroup$

Another series approach might offer a hint:

$$\int_0^1 x^pdp=\frac{1}{p+1}$$

$$\int_0^1 x^{ak} x^ldp=\frac{1}{ak+l+1}$$

$$\int_0^1 \frac{\ln(1+x^a)}{1+x}dx=\sum_{k=1}^{\infty} \sum_{l=0}^{\infty} \frac{(-1)^{k+l+1}}{k(ak+l+1)}=\sum_{k=1}^{\infty} \frac{(-1)^{k+1}}{k} \Phi(-1,1,ak+1)$$

Here $\Phi$ is Lerch Trancendent. I only consider $a>0$, otherwise this series might diverge. But really, we only need the case $a>1$ as you showed.


The double sum, despite being unwieldy, offers some insight into $f(a)$. For example, we can guess that for $a \to +\infty$ the asymptotic is $f(a) \to \frac{\pi^2}{12a}$:

$$\frac{1}{a} \sum_{k=1}^{\infty} \sum_{l=1}^{\infty} \frac{(-1)^{k+l}}{k^2+kl/a} \asymp^{a \to +\infty} \frac{1}{a} \sum_{k=1}^{\infty} \frac{(-1)^{k+1}}{k^2}=\frac{\pi^2}{12a}$$

This is not a proof! But the asymptotic is right, as is shown in this answer for a related integral.


I really suggest you read the links provided in the comments to find out about possible closed forms, but just in case I aslo compile the simplest cases with closed forms here:

$$ \begin{matrix} a & f(a) \\ -2 & \dfrac{7 \pi ^2}{48}+\dfrac{3 \ln ^2 2}{4} \\ -1 & \dfrac{ \pi ^2}{12}+\dfrac{\ln ^2 2}{2}\\ -\dfrac{1}{2} & \dfrac{\pi ^2}{16}+\dfrac{\ln ^2 2}{4}\\ 0 & \ln ^2 2 \\ \dfrac{1}{2} & \dfrac{\pi ^2}{48}+\dfrac{\ln ^2 2}{4} \\ 1 & \dfrac{\ln ^2 2}{2} \\ 2 & -\dfrac{\pi ^2}{48}+\dfrac{3 \ln ^2 2}{4}\\ \end{matrix} $$


See also this answer for a more comprehensive approach

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.